Wild foods’ role in human diets - Sunderland, T.C.H. (Springer, 2023)
Rural dietary diversity largely depends on farmers’ access to wild food and forests. The policy environment on achieving global food security must consider managing multi-functional landscapes for a diverse array of goods and services, including food.